Spiritual Values and Accounting Practices of Christian Charity Organizations: What is their Role and Meaning? - Setiawan, Ricky Yunisar; Ginting, Rafles; Anandita, Rissa; Robiansyah, Anton; Jatmika, Windy (KEUNIS, 2025)
The Christian Charity Organization is dedicated to establishing social networks and cultivating trust among its followers through activities rooted in Christian values, demonstrating transparency and accountability to God, donors, management, and members. This qualitative case study aims to unveil the influence of spiritual values on the accountability practices within the organization. Data collection involves interviews, document analysis, and observation, followed by a thorough analysis process. The findings highlight that values such as awareness, dignity, meaningfulness, transcendence, truth, peace, and wisdom instill confidence in the organization's accountability towards God, donors, management, and members. The study sheds light on the vital role of accounting practices in public organizations for fostering societal trust. However, limitations include the case study method and the focus on the Christian Charity Organization. Future research should consider phenomenological or ethnographic approaches and encompass diverse identities within nonprofit organizations